Analysis of Basic School Education Policies Related to Learning During Pandemic in Serang City - Imas Mastoah; Muhamad Syarif Sumantri; Arita Marini (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2021)
This study aims to analyze the policies of education in primary school related to learning during a pandemic in Serang city. The method used is a descriptive qualitative method using this type of survey. Techniques in data collection use techniques to find information in indirect communication in using technology-based media intermediaries by using questionnaires in Google Form. Respondents involved in this study were in An-Nur Modern Islamic School with 90 students, eight teaching staff, one school principal, and five educational staff. The result showed that education is divided into the family environment (informal education), school environment (formal education), and community environment (nonformal education). Then education policy is seen as a set of rules that the government has to create education that follows the ideas to reach the desired goal; alignments here include politics, budget, empowerment, and rules. In the implementation of education policy, there are seven steps: analyzing the situation, making some new policy, evaluating policy choices, making decisions, planning the implementation, assessing the impact of policy implementation, and determining the subsequent policy cycles.